Students' Critical Thinking Ability Through the Problem-Based Learning Model Assisted by Quizizz Reviewed from Learning - Salsabil Qoriroh; Mulyono Mulyono (Indo Publishing, 2026)
This research investigated the effectiveness of the Problem-Based Learning (PBL) model assisted by Quizizz in enhancing students' critical thinking skills and described critical thinking abilities across different learning styles (visual, auditory, kinesthetic). Employing a mixed-method approach with an explanatory sequential strategy, the study initially collected quantitative data through critical thinking tests, followed by qualitative data from learning style questionnaires and student interviews. The population comprised all seventh-grade students at SMP Negeri 23 Semarang in the /2025 academic year, with class VII C as the experimental group using PBL with Quizizz (32 students) and class VII A as the control group using Discovery Learning (32 students). Results show that the PBL-Quizizz model significantly improved critical thinking, with the experimental group achieving a higher average score (87.87) and classical completeness (93.75%) compared to the control group (77.46; 59.38%). All learning styles generally met critical thinking indicators, though some students struggled with problem comprehension.